Peritoneum and omentum are natural reservoirs for chondrocytes of osteochondral autografts: A comparative animal study - Kadir Buyukdogan; Mahmut Nedim Doral; Onur Bilge; Egemen Turhan; Gazi Huri; Mustafa Fevzi Sargon (Acta Orthopaedica et Traumatologica Turcica)
Objective: The purpose of this study was to investigate the effects of the omentum, peritoneum, paratenon and skeletal muscle on the proliferation of the cartilage tissue using rabbit model as an in vivo culture medium. Methods: 6 months old forty-five New Zealand rabbits were randomized into omentum, peritoneum, muscle, and Achilles paratenon groups. Standard sized osteochondral grafts were harvested from right knees and immediately placed into the specified tissues. Control group was fresh cartilage at the end of follow-up. After five months, samples were collected and evaluated macroscopically by measuring their dimensions (vertical = D1, horizontal = D2, and depth = D3) and volumes, and histologically by counting the chondrocyte number using camera lucida method. Results: Macroscopically, increase in mean values for D1 and D2 dimensions of specimens from paratenon and omentum compared to pretransplant dimensions was statistically significant (p < 0.05). Although, volume measurements were higher in omentum and peritoneum group compared to pretransplant dimensions, increase was not significant (p > 0.05). Histologically, mean chondrocyte count was 14.0 ± 0.6 in fresh articular cartilage. Mean chondrocyte counts were 14.4 ± 0.9 in omentum group, 15.4 ± 1.0 in peritoneum group, 9.7 ± 1.3 in muscle group and 9.2 ± 0.4 in Achilles paratenon group respectively. However, mean chondrocyte counts were higher in samples of omentum and peritoneum group compared to fresh articular cartilage, increase was not statistically significant (p > 0.05). Discussion: Transplantation of the cartilage grafts into mesothelium enhanced the chondrocyte counts and volumes compared with the pretransplant measurements. Mesothelium may have the potential to be used as an in vivo culture medium for osteochondral tissue growth. Keywords: Cartilage preservation, Mesothelium, Chondrocyte, Knee